GAMBARAN PERBEDAAN KARATERISTIK PETUGAS PUSKESMAS DENGAN CAKUPAN PENEMUAN PNEUMONIA BALITA TERTINGGI DAN TERENDAH (STUDI 10 PUSKESMAS KABUPATEN TEMANGGUNG) - Hasyanah, Uswatun; Yuliawati, Sri; Hestiningsih, Retno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Pneumonia is a process of acute infection associated with lung tissue (alveoli), which is one of the biggest causes of child death in the world. One of the efforts made by the government is to reduce the incidence of toddler pneumonia by carrying out a program of finding toddler pneumonia. Toddler pneumonia discovery program has a target that has been set nationally. Community Health Centers in Temanggung Regency have very significant differences in coverage of toddler pneumonia findings between primary healthcare that have reached and have not yet reached the target.The purpose of this study was to describe the diferences officer factors in public health centers with high and low coverage of infant pneumonia findings in Temanggung Regency.This type of research uses observational analytics using cross sectional methods. The sample of this study was 10 primary Healthcare Temanggung District. The results of the study the difference between high and low coverage health centers, the knowledge factor of officers was 72.0% and 62.0%, the motivation of the officers was 64.0% and 73.0%, the activeness of officers was 64.0% and 73.0%, work officers are 80.0% and 100.0%. Published to the Health Office to refresh knowledge about toddler pneumonia to harmonize understanding of toddler pneumonia and how to detect toddler pneumonia.